2008
DOI: 10.1080/17449200802473131
|View full text |Cite
|
Sign up to set email alerts
|

Fit for prison: Special population health and fitness programme evaluation

Abstract: The health and fitness programme positively impacts on the health of inmates with a chronic illness. A further study with a larger sample size would be productive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
(16 reference statements)
3
13
0
6
Order By: Relevance
“…The negative health behaviors documented in this paper can, if modified, reduce many future health risks. Our findings strengthen the argument for prisons to enable exercise as a public health intervention, with demonstrated benefits including improved physical and mental health [21,27,28,29,30,31,32], and reduced aggression [33], and inmate-identified benefits in one review including improved self-esteem, confidence, and the construction of a new identity [81]. Incarceration should be seen as an opportunity for positive behavior change, and it is encouraging that inmates with pre-incarceration harmful substance use seem particularly able to adopt such changes.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The negative health behaviors documented in this paper can, if modified, reduce many future health risks. Our findings strengthen the argument for prisons to enable exercise as a public health intervention, with demonstrated benefits including improved physical and mental health [21,27,28,29,30,31,32], and reduced aggression [33], and inmate-identified benefits in one review including improved self-esteem, confidence, and the construction of a new identity [81]. Incarceration should be seen as an opportunity for positive behavior change, and it is encouraging that inmates with pre-incarceration harmful substance use seem particularly able to adopt such changes.…”
Section: Discussionsupporting
confidence: 73%
“…Many of the barriers to exercise identified by substance users, such as a lack of time, transportation, or finances [8,26] can be easily removed in incarceration settings. Exercise interventions among inmates have increased fitness and functional cardiorespiratory capacity [27,28,29,30], improved psychological well-being [21,28,31,32], and reduced aggression [33]. Only two of these studies reported on inmates with some sort of harmful substance use: 105 inmates with “substance abuse problems” pre-incarceration, no diagnosis reported, self-reported improved physical fitness and alleviated anxiety, stress, and depression [28], and 19 inmates in methadone maintenance treatment improved strength and cardiorespiratory capacity [30].…”
Section: Introductionmentioning
confidence: 99%
“…Our rates of attendance (77%) and exercise dropout (48%) were similar to those reported in previous studies of combined exercise in prison, which ranged from 57% to 75% 8,10,24 and from 12% to 50%, 810,24 respectively. Interestingly, all of these studies were randomized controlled trials of group-based interventions in men.…”
Section: Discussionsupporting
confidence: 89%
“…6 Given that prison inmates also do not undertake regular physical activities, 7 it is possible that the combination of being a prison inmate and having a psychiatric disorder may exacerbate the tendency towards physical inactivity. There are very few peer-review studies on increasing exercise in the prison population, [8][9][10] and none investigating exclusively prisoners with psychiatric disorders. Understanding the feasibility and effects of exercise-based interventions on the health of prison inmates with psychiatric disorders is both a challenge and an opportunity for the public health and scientific community.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, CRT allows to reach better aerobic capacity, which promotes and maintains health, and an optimal caloric expenditure [37]. This training protocol guarantees a strength level sufficient to sustain daily living that is made up of mostly sub-maximal-strength tasks and a good level of flexibility and agility that could help this special population to reduce injuries and consequent chronic diseases [38].…”
Section: Discussionmentioning
confidence: 99%